Low Vitamin D Status Is Associated with Epithelial–Mesenchymal Transition in Patients with Chronic Obstructive Pulmonary Disease - Fei, Jun; Fu, Lin; Cao, Wei; Hu, Biao; Zhao, Hui; Li, Jia-Bin (The Journal of immunology (1950), 2019)
Vitamin D deficiency is correlated with the increased morbidity of chronic obstructive pulmonary disease (COPD). However, the mechanisms underlying these effects have largely remained elusive. This study analyzed the correlations among COPD, vitamin D concentration, and epithelial–mesenchymal transition (EMT). Ninety-five patients with newly diagnosed COPD and 190 age- and sex-matched healthy subjects were recruited for this research. Serum 25(OH)D levels were detected, and pulmonary EMT biomarkers and TGF-β/Smad signaling were evaluated. Serum 25(OH)D level was remarkably decreased in COPD patients compared with that in control subjects. Furthermore, serum 25(OH)D concentration gradually decreased in COPD patients ranging from grade 1–2 to 4. However, reduced expression of the epithelial biomarker E-cadherin and increased expression of the mesenchymal biomarkers vimentin and α-SMA were found in COPD patients. Mechanistic analysis showed that pulmonary nuclear vitamin D receptor (VDR) was decreased in patients with COPD. In contrast, TGF-β/Smad signaling was obviously activated in COPD patients. Furthermore, the level of serum TGF-β in COPD patients increased in parallel with COPD severity. Serum 25(OH)D concentration was inversely associated with TGF-β levels in COPD patients. In vitro experiments showed that active vitamin D3 inhibits TGF-β–induced Smad2/3 phosphorylation in MRC-5 cells. Furthermore, vitamin D concentration was inversely correlated with TGF-β/Smad signaling and EMT in COPD patients, suggesting EMT as a vital mediator of COPD development in patients with low vitamin D concentrations.